PEMUSNAHAN BARANG BUKTI DI TINGKAT PENYIDIKAN TINDAK PIDANA PERIKANAN BERDASARKAN UNDANG-UNDANG NOMOR 45 TAHUN 2009 TENTANG PERIKANAN - Hamidi, Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Problems often occur in cases of violation of the law in the territorial waters of criminal offense of illegal fishing in the sea area of law violations in the form of illegal fishing, a license which trumped, erta use fishing gear that damages the conservation and management of fish resources. In such cases the foreign vessels caught in the act illegal fishing in the region ZEE Indonesian will be given a decisive action in the form of sinking fishing. The purpose of this thesis, namely: First, whether the destruction of evidence such as ships can be justified if review of the presumption of innocence, Second, the impact on the judicial process regarding the evidence has been destroyed at the investigation stage of this type of research can be classified in this type of normative research. Namely the study of the principles of law. Systematics of law, the degree of synchronization of law, legal history and comparative law. As in this case the author conducts legal research normative principles of law, namely by looking at the Law Number 45 Year 2009 on Fisheries in conducting this research using secondary data, which consists of primary data, secondary data, and the data tertiary. In conducting the study, researchers used a qualitative analysis of the results of research that produces descriptive data that is what is stated in writing.The sinking of the ship on the stage of investigation conducted by the investigator based on the rule of law, namely Law Number 45 Year 2009 on Fisheries, of course we also need to assess whether laws regulating this matter in accordance with the legal principles that apply for each of the rules legislation made must not conflict with the principles of the existing law. In addition, the already sinking barrage evidence of the ship at the stage of investigation is affecting the proceedings, both in terms of the objectivity of the judge who handled the case, so the judge should be convicted defendant and thus it is the evidence of the ship in the judgment in seized to be destroyed, because if the judges decide the defendant not guilty, then evidence ships can not be taken to be destroyed, while the ship has been destroyed.Keywords : Extermination – Evidence – Fishing Boats